TEACHER STRATEGIES FOR CULTIVATING BASIC SCIENCE PROCESS SKILLS IN STATIC FLUID LEARNING: A NATURALISTIC QUALITATIVE INQUIRY - Yusnidar, Yusnidar; Kurniawan, Dwi Agus; Pramitha, Sarah (LPPM Universitas Jambi, 2026)
This study aimed to explore teacher strategies for cultivating students' Basic Science Process Skills during static fluid learning in a natural classroom setting. A naturalistic qualitative approach was employed at Senior High School 10 Kota Jambi, involving one physics teacher and students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña supported by NVivo 14 software. The findings revealed that the teacher systematically cultivated students' Basic Science Process Skills through demonstrations, structured observations, laboratory experiments, collaborative discussions, and laboratory worksheets. These strategies effectively developed students' abilities in observing, classifying, measuring, communicating, predicting, and drawing conclusions throughout the learning process. The originality of this study lies in providing comprehensive qualitative evidence of teacher strategies that cultivate all six Basic Science Process Skills through authentic physics classroom practices supported by NVivo-assisted analysis. The findings contribute to physics education by offering practical guidance for designing inquiry-oriented learning that systematically strengthens students’ science process skills.